Religion and nationalism in global perspective - Soper, J. Christopher (Cambridge studies in social theory, religion, and politics, 2018)
A theory of religion and nationalism -- United states: stable civil-religious nationalism -- Israel: unstable civil-religious nationalism -- Greece: stable religious nationalism -- Malaysia: unstable religious nationalism -- Uruguay: stable secular nationalism -- India: unstable secular nationalism -- Pitfalls and opportunities on the religious path to nationalism